E-Government Policy to give their Citizens a ‘Citizen Index Score’ based on which Citizens can Take Part as Voters in the Election - Younus, Muhammad; Purwaningsih, Titin; Eka Rahmawati, Dian; Suswanta; Nurmandi, Achmad; Gul, Hajira (Jurnal Ilmu Pemerintahan : Kajian Ilmu Pemerintahan dan Politik Daerah, 2023)
This study aims to determine the framework related to the Government Policy of determining the Average weightage against each citizen of the country, which will decide the value or impact of the Individual Vote given to the Candidate by the Voter in the Election process and similarly that Average Weightage will be deciding the Election Candidate validity to run in the Election. Researchers are doing research work in this specific use case using ‘Qualitative Research.’ This research data was taken from social media, Online Media, Websites, Journals, and Articles and then represented in descriptive format. This study indicates that the creation of this Policy will surely improve the quality of the Election process in the country and build more trust in the Citizens in the Electoral Process. There are several milestones that need to be fulfilled for the development and successful implementation of this policy—first, the analysis and determining the critical indicators required for the Average Weightage calculation. Second, the selection of the medium for the solution. Finally, then start the development of the solution based on the analysis. This paper is limited to the extent to which the problem is clearly described, then proposing the solution and how it should work, and lastly, what benefits the solution will be given to resolve the challenge the current Election process is facing.